Ignacy Sachs’s concepts and the contribution to studies in Local Development: a small reflection - Ribeiro Coutinho, Dolores Pereira; Pompeu, Adriano Marinheiro; de Oliveira Junior, Marcos Fermau (Interações, 2016)
Development studies of the deal with the pillars of sustainability and sustainable developmentis broader in your vision format field. The aim of this scientific paper is to contextualize intellectual and professional trajectory of Ignacy Sachs, to understand how was the construction of concepts that include economic, social and environmental fundamental aspects to studies in Local Development. The bibliographical research used on the spiral of knowledge is to show how it is consolidated ideas starting from local studies.